2016
DOI: 10.1016/j.jsxm.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Transgender Depends on the “Case” Definition: A Systematic Review

Abstract: Background We conducted a systematic review and meta-analysis to evaluate how various definitions of “transgender” may affect prevalence estimates. Methods PubMed, Embase, and Medline were searched to identify studies reporting prevalence estimates of transgender in a population. All studies were grouped based on the case definition applied to the numerator. Summary estimates were derived using a random-effects model for total prevalence of transgender and for male-to-female (MTF) and female-to-male (FTM) su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
157
0
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 256 publications
(174 citation statements)
references
References 43 publications
1
157
0
16
Order By: Relevance
“…6 Third, most extant population-level studies did not have adequate samples to examine the health of transgender subpopulations: transgender women (male-tofemale, MTF); transgender men (female-to-male, FTM); and gender-nonconforming (GNC) people. 7 This gap in the literature is significant, as the lived experiences of these populations can be markedly different, both in exposure to interpersonal and structural cissexism (discrimination and stigma against TGNC people), and the amount and quality of engagement with the healthcare system. 3 For example, the National Transgender Discrimination Survey found that GNC people faced more discrimination in medical care and worse health than other transgender groups.…”
Section: Introductionmentioning
confidence: 99%
“…6 Third, most extant population-level studies did not have adequate samples to examine the health of transgender subpopulations: transgender women (male-tofemale, MTF); transgender men (female-to-male, FTM); and gender-nonconforming (GNC) people. 7 This gap in the literature is significant, as the lived experiences of these populations can be markedly different, both in exposure to interpersonal and structural cissexism (discrimination and stigma against TGNC people), and the amount and quality of engagement with the healthcare system. 3 For example, the National Transgender Discrimination Survey found that GNC people faced more discrimination in medical care and worse health than other transgender groups.…”
Section: Introductionmentioning
confidence: 99%
“…4 Unfortunately, because of limitations of the study design, the researchers were unable to comment on whether these people were all transgender women; however, the veteran population tends to be predominantly men. In a 2016 systematic review of 29 studies, 5 the prevalence of transgender women was roughly 5–20 per 100 000 when diagnostic codes or requests for medical treatment were used, or as high as 521 per 100 000 people if based on self-identification.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of clinically established transsexualism varies from 0.7/100,000 in Iran to 100/100,000 in Iceland, with a mean value of 9.2/100,000. [3][4][5] However, a meta-analysis of studies about transsexualism epidemiology, which were based on self-reported transgender identity, revealed a much higher transgender occurrence of 355/100,000. 4 Therefore, it may be suspected that gender incongruence is highly underdiagnosed.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] However, a meta-analysis of studies about transsexualism epidemiology, which were based on self-reported transgender identity, revealed a much higher transgender occurrence of 355/100,000. 4 Therefore, it may be suspected that gender incongruence is highly underdiagnosed. Most of the studies report a higher number of MTF transsexuals than of FTM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation